2015
DOI: 10.1002/lt.24117
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of biomarkers and Milan criteria for predicting hepatocellular carcinoma recurrence after liver transplantation

Abstract: Growing evidence suggests that pretransplant alpha-fetoprotein (AFP) predicts outcomes of hepatocellular carcinoma (HCC) patients treated with liver transplantation. We aimed to determine whether pretransplant AFP, Lens culinaris agglutinin-reactive alpha-fetoprotein (AFP-L3), and des-gamma-carboxyprothrombin (DCP) predicted HCC recurrence after transplantation. A retrospective cohort study of 313 HCC patients undergoing transplantation between 2000 and 2008 was conducted, and 48 (15.3%) developed recurrence d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
89
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 19 publications
5
89
0
Order By: Relevance
“…Research by Varona et al (2015) supplements the argument made by Chaiteerakij et al (2015), in terms of the AFP biomarker. These two studies agree that biomarkers should be used in addition to criteria methods, but the studies propose different levels of AFP as the indicator of recurrence.…”
Section: Patientsmentioning
confidence: 80%
See 4 more Smart Citations
“…Research by Varona et al (2015) supplements the argument made by Chaiteerakij et al (2015), in terms of the AFP biomarker. These two studies agree that biomarkers should be used in addition to criteria methods, but the studies propose different levels of AFP as the indicator of recurrence.…”
Section: Patientsmentioning
confidence: 80%
“…Research performed by Fisher et al (2007), Bonadio et al (2015), and Kornberg et al (2015) identified higher incidence, reported at 18%, 22%, and 23.3%, respectively. The third range of incidence was significantly higher, with Chaiteerakij et al (2015) reporting 32%. No consensus is given for an exact range of incidence, but research suggestions a common range of 6 to 20%, with outliers of 30% or more.…”
Section: Incidencementioning
confidence: 91%
See 3 more Smart Citations